Legal Accountability in the Lapindo Mudflow Case: Assessing Liability Between Strict Liability and Fault-Based Responsibility - Deru, Kesya Chantall Alisya; Eijileen, Brigitta Kezia; Kusuma, Katya Aiko (Law Review, 2024)
Strict liability is a form of liability where a party is held accountable for the damage or harm caused by action of the party regardless of intent or fault.  Strict liability is typically imposed in industries where inherently risky activities are undertaken, e.g., hazardous waste disposal, nuclear power, or the manufacture of chemicals. This research evaluates if the concept of strict liability is appropriate for the Lapindo mudflow. A qualitative approach allows for an in-depth analysis of the legal principles and arguments that have underpinned the handling of the Lapindo case. The application of strict liability principle is connected with PT Lapindo Brantas, a construction company appointed by BPMIGAS to perform oil drilling and natural gas. The eruption of mudflow was caused by the drilling activities of PT Lapindo Brantas, which were risky in nature and led to devastating consequences on the surrounding communities. Since the drilling activities are perilous in nature, particularly in an area of high subsurface instability potential, strict liability could be imposed. The damage caused by the mudflow—property loss, people displacement, and degradation of the environment—was the direct result of the activities of the company. In strict liability, PT Lapindo would have been responsible for the harm, regardless of whether their action was negligent or intentional, because drilling in this area can be considered an inherently dangerous act.